Prospect of umbilical cord mesenchymal stem cell culture waste in regenerative medicine - Jeanne Adiwinata Pawitan; Melisa Leviana; Dewi Sukmawati; Isabella Kurnia Liem; Ria Margiana; Twidy Tarcisia (Journal of Global Pharma Technology, 2017)
Abstract: Objective:to analyzevarious growth factor (GF) content in umbilical cord derived mesenchymal stem cell (UC-MSC) culture waste at harvest.Methods: We cultured UC- MSCs in complete medium, and collected the medium waste at harvests.  We noted the time of harvests, and measured the concentrations of EGF, VEGF, NGF and Pl GF in the various medium wastes using ELISA method. We grouped GF concentrations according to various culture lengthsat harvest, and calculated themean values and standard deviations of the various GF. We compareddescriptively the GF concentrations at various culture lengths at harvests to conclude which condition yielded the overall highest GF concentration.Results: EGF, VEGF and PlGF concentrations were highest at harvest day-3, whileNGF concentration was the highest at harvest-day-5, respectively. Therefore, overall highest concentration of most GF was at harvest day 3.Conclusion:UC-MSC culture waste at harvest day-3 containedEGF, VEGF, NGF and PlGF, which might be used in regenerative medicine.